تصميم ألعاب لغوية لتعليم اللغة العربية من خلال الكلمات الإندونيسية ذات أصل عربي في القاموس الإندونيسي الكبير - Wildan FM; Said Hassan Nassila (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
The purpose of this study is to point out absorbed Indonesian Words from Arabic in “ KBBI ” dictionary from the “ F ” to “ I ”, and to know meaning’s change from each words in Indonesian language, and also the aim from this study is how to design language games from these words to help first grade students in their study for Arabic.This study is including in qualitative research and are also called qualitative and descriptive method. To write this study research used the descriptive analitycal method. And this study has proved absorbed Indonesian words from arabic in ( KBBI ) Dictionary from “ F ” to “ I ” and the number of these words is two hundred (171) words. And the reseach found meaning’s change when the words are absorbed from arabic to Indonesian language, and these changes are in four types. And also the research found methods of designing language games from these words to help first grade students in their study for Arabic, and these method are in the four language skills.